In situ observation of electrical property of thin-layer black phosphorus based on dry transfer method. (10th March 2016) - Xin, Xin; Zhao, Hai-Ming; Cao, Hui-Wen; Tian, He; Yang, Yi; Ren, Tian-Ling
Abstract: The electrical property of thin-layer black phosphorus (BP) was explored using a simple dry transfer method, which greatly reduced the fabrication time to carry out electrical measurement starting from an initial state with little degradation. As a result, the as-prepared BP field-effect transistor (FET) exhibited a high on/off ratio exceeding 10 4 and a high hole mobility of 380 cm 2 /(V·s). The time-dependent electrical property of BP indicated a declining and recovering process, caused by the degradation and doping effect. Finally, it was demonstrated that the degradation and large hysteresis of BP FET could be modified by covering a thin Al2 O3 layer.